Patterns of Multimodality Management of Gastric Cancer—Single Institutional Experience of 372 Cases From a Tertiary Care Center in North India - Kumar, Sunil; Kumar, Naveen; Deo, Suryanarayana; Bhoriwal, Sandeep; Mandal, Amitabha; Sharma, Atul; Pathy, Sushmita; Das, Prasenjit; Thulkar, Sanjay; Bhatnagar, Sushma (Frontiers in Oncology, 2022)
Introduction: Worldwide gastric cancer is the 5th most commonly diagnosed cancer and the leading cause of gastrointestinal cancer-related deaths. Alone surgery provides long term survival improvements in 20% of the patients with local advanced gastric cancer. The results can be improved considering multimodal management including chemotherapy and radiotherapy. However, in low middle-income countries like India, multimodal management is challenging. Herein, we evaluated the experience of multimodal management of gastric cancer and the long term outcome. Methods: Retrospective analysis of the data of 372 patients was done from a prospectively maintained computerized database from 1994 to 2021. Records were analysed for demographic details, treatment patterns, recurrences and long term outcomes(DFS &OS). Statistical analysis was one with packages SPSS version 26 (IBM Corp, Chicago, Illinois, USA). Results: This study included 372 patients. The mean age of the patients was 54.07. Total 307 patients (82.5%) cases were operated upfront, 45(12%) received NACT and 20(5.5%) of cases underwent the palliative procedure. A total of 53.2% underwent curative resection. . R0 resection rate was achieved in 95% of patients. 72.58% of patients required adjuvant treatment and the majority of the patients underwent chemoradiotherapy. The most common site of metastasis was the liver. The Median follow up was 50.16 months. The 3-year disease-free and overall survivals were 36.28% & 67.8% and the 5-year disease-free and overall survivals were 30.15% & 37.7% respectively. Conclusion: Our study suggested that multimodal management is required in locally advanced gastric cancer to achieve good long-term outcomes. The treatment sequence can be tailored based on the available resources